Distribution of serogroup specific antibodies against leptospirosis in livestock in Odisha - BALAMURUGAN, V; VEENA, S; THIRUMALESH, S R A; ALAMURI, A; SRIDEVI, R; SENGUPTA, P P; GOVINDARAJ, G; NAGALINGAM, M; HEMADRI, D; GAJENDRAGAD, M R; RAHMAN, H (The Indian Journal of Animal Sciences, 2017)
The study was conducted to identify epidemiological sero-distribution of Leptospira serovars representing serogroups of antibodies in Odisha, Eastern part of India. Samples were collected from livestock during 2011-2014. A total of 537 non-purposive random serum samples from 12 districts in Odisha were tested at 1:100 dilutions in microscopic agglutination test (MAT) using live antigens of 18 reference Leptospira serovars. The overall prevalence of 36.69% (197/537) with 36.13% in cattle, 54.28% in buffaloes, 28.33% in goats and 44.44% in sheep was observed. Out of 197 reacted sera, 100 samples showed reactivity with more than one serovars representing 50.76% prevalence of multiple serovars. On analysis, the seroprevalence of leptospirosis in cattle (·2 = 63.41, P<0.01), buffaloes (·2 = 14.68, P <0.01), sheep (·2 = 54.66, P <0.01) and goats (·2 = 36.27, P <0.01) across different regions are significantly dependent. The predominant Leptospira serogroup specific antibodies against major serovars representing Hardjo (30.4%), Tarassovi (20.8%), Australis (19.19%), Bankinang (18.18%), Pomona (16.66%), Kaup (15.65%), Hebdomadis (11.11%), Pyrogenes (10.1%), Bataviae (9.59%), Icterohaemorrhagiae (9.09%), Shermani (7.57%), Djasiman/Javanica (6.56%), Hurstbridge (5.55%), Grippotyphosa (4.54%), Panama (4.04%), Canicola (3.03%) and Copenhageni (2.02%) against frequency distribution were noticed. The overall prevalence of antibodies detected against the serovars Hardjo, Tarassovi, Australis, Bankinang, Pomona, Kaup, Hebdomadis and Hurstbridge representing specific serogroups suggested that these serovars may be of use in the reference panels of Leptospira antigen in the MAT for this region in both human and animal state or district disease diagnostic laboratories.